Total bodyweight and sex both drive pharmacokinetic variability of fluconazole in obese adults - Chen, Lu; van Rhee, Koen P; Wasmann, Roeland E; Krekels, Elke H J; Wiezer, Marinus J; van Dongen, Eric P A; Verweij, Paul E; van der Linden, Paul D; Brüggemann, Roger J; Knibbe, Catherijne A J (Journal of antimicrobial chemotherapy, 2022)
Fluconazole is commonly used to treat or prevent fungal infections. It is typically used orally but in critical situations, IV administration is needed. Obesity may influence the pharmacokinetics and therapeutic efficacy of a drug. In this study, we aim to assess the impact of obesity on fluconazole pharmacokinetics given orally or IV to guide dose adjustments for the obese population. We performed a prospective pharmacokinetic study with intensive sampling in obese subjects undergoing bariatric surgery (n = 17, BMI ≥ 35 kg/m2) and non-obese healthy controls (n = 8, 18.5 ≤ BMI < 30.0 kg/m2). Participants received a semi-simultaneous oral dose of 400 mg fluconazole capsules, followed after 2 h by 400 mg IV. Population pharmacokinetic modelling and simulation were performed using NONMEM 7.3. A total of 421 fluconazole concentrations in 25 participants (total bodyweight 61.0-174 kg) until 48 h after dosing were obtained. An estimated bioavailability of 87.5% was found for both obese and non-obese subjects, with a 95% distribution interval of 43.9%-98.4%. With increasing total bodyweight, both higher CL and Vd were found. Sex also significantly impacted Vd, being 27% larger in male compared with female participants. In our population of obese but otherwise healthy individuals, obesity clearly alters the pharmacokinetics of fluconazole, which puts severely obese adults, particularly if male, at risk of suboptimal exposure, for which adjusted doses are proposed.